2003
DOI: 10.1021/ic026118t
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Carbon Fragments into P(III)−N Bonds in Aminophosphines and Aminobis(phosphines):  Synthesis, Reactivity, and Coordination Chemistry of Resulting Phosphine Oxide Derivatives. Crystal and Molecular Structures of (Ph2P(O)CH2)2NR (R = Me, nPr, nBu), Ph2P(O)CH(OH)nPr, and cis-[MoO2Cl2{(Ph2P(O)CH2)2NEt-κOO}]

Abstract: Reactions of N-aryl and N-alicyclic derivatives of aminophosphines with paraformaldehyde lead to methylene insertion into P-N bond followed by oxidation of phosphorus from the P(III) to P(V) state. When N-alkyl derivatives are reacted with paraformaldehyde, dimerization takes place to afford bis(phosphine oxide)s of the type Ph(2)P(O)CH(2)N(R)CH(2)P(O)Ph(2) (R = Me, (n)Pr, (n)Bu). Aminobis(phosphines) also undergo methylene insertion when treated with paraformaldehyde to give bis(phosphine oxides) Ph(2)P(O)CH(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 45 publications
(51 reference statements)
3
15
0
Order By: Relevance
“…These show typical aromatic character. The distance of P1O1 (1.494 Å) is very close to P=O bond length (1.493 Å) reported in the literature [3]. There are no intermolecular p-p stacking interactions in the crystal structure.…”
Section: Discussionsupporting
confidence: 82%
“…These show typical aromatic character. The distance of P1O1 (1.494 Å) is very close to P=O bond length (1.493 Å) reported in the literature [3]. There are no intermolecular p-p stacking interactions in the crystal structure.…”
Section: Discussionsupporting
confidence: 82%
“…The use of phosphorous acid as the P-reactant led to bis(phosphonic acids) [16,17]. Bis(phosphinoxido)derivatives were synthesized via a surprising methylene insertion reaction into a PeN bond followed by oxidation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we suggested a mechanism for the methylene insertion into the P-N bonds in aminophosphines involving a Staudinger-Wittig pathway, in which (c) proton transfer occurs from nitrogen to the phosphorus center to give R 2 P(O)H as an intermediate [28]. However, this mechanism fails to explain the insertion observed in non-proton containing aminophosphines such as RN(PPh 2 ) 2 and Ph 2 PN(C 2 H 4 ) 2 PPh 2 , hence it was concluded that the presence of the NH group is not a requirement [29,30]. The reactivity of cis-[{P(l-N t Bu)N(H) t Bu} 2 ] towards paraformaldehyde indicates that the preferential exocyclic P-N bond insertion is essentially due to the relatively more basic nature of the amide nitrogens compared to the ring nitrogen atoms.…”
Section: Chalcogen Derivativesmentioning
confidence: 99%